2006
DOI: 10.21273/hortsci.41.3.759
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Induction and Characterization of Tetraploid Lychnis senno Siebold et Zucc.

Abstract: In this study, in vitro induction of tetraploid Lychnis senno Siebold et Zucc. and its cytological and morphological characterization were conducted. For polyploid induction, nodal segments with axillary buds from in vitro grown plants were kept for 3 days in MS (Murashige and Skoog, 1962) liquid or solid media added with a series of concentrations of colchicine. Out of total 588 recovered plants, 15 tetraploids and 6 mixoploids determined by flow cytometry analysis were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
(14 reference statements)
5
23
0
Order By: Relevance
“…Another promising approach is the use of colchicine to obtain polyploid plants from in vitro cultures, so the production of valuable secondary metabolites could be increased. This approach was successful with L. senno in vitro cultures, yielding tetraploids differing from diploid plants, at least morphologically (Chen et al, 2006a). L. senno is an example of another rare species from genus Lychnis for which in vitro propagation system has been also established.…”
Section: Micropropagation and In Vitro Culturesmentioning
confidence: 99%
“…Another promising approach is the use of colchicine to obtain polyploid plants from in vitro cultures, so the production of valuable secondary metabolites could be increased. This approach was successful with L. senno in vitro cultures, yielding tetraploids differing from diploid plants, at least morphologically (Chen et al, 2006a). L. senno is an example of another rare species from genus Lychnis for which in vitro propagation system has been also established.…”
Section: Micropropagation and In Vitro Culturesmentioning
confidence: 99%
“…Another approach to manage this problem is to develop triploid clones after crossing between tetraploid and diploid parents. From a horticultural point of view, such triploids are expected to be superior to their diploid counterparts, with a higher yield, more vigorous growth, and seedlessness or less-seeded characteristics, making them more attractive to consumers [6]. It has been reported that a tetraploid pumpkin fruit's weight is 2.9 kg with fewer seeds (30), while that of diploids is 2.2 kg with more seeds (122) [7].…”
mentioning
confidence: 99%
“…Chromosome doubling has been used extensively as a tool for creating novelty in ornamental crops (Ascough et al, 2008;Hancock, 1997;Väinölä, 2000). Horticultural benefits of polyploidization include thicker stems and leaves, larger and more intensely colored flowers, novel flower coloration, lower phenotypic variability, a protracted flowering period, a more compact growth habit, improved drought tolerance, and raised photosynthetic capacity (Chen et al, 2006;Hancock, 1997;Sparnaaij, 1979). Because naturally occurring polyploid genotypes are usually unavailable for breeding programs, polyploidy is typically induced through mitotic spindle inhibition or microtubule polymerization, often by exposure to colchicine (Caperta et al, 2006;Doležel et al, 2004).…”
mentioning
confidence: 99%
“…However, such colchicine-induced polyploidy is characterized by low induction rates and a high frequency of chimeras (Cohen and Yao, 1996;Galbraith et al, 1997) with the efficacy of transformation in vitro depending on the concentration of colchicine, the duration of exposure, explant type, and tissue penetrability (Allum et al, 2007). Colchicine has been used effectively in the concentration range 0.25 mM [0.00001% (w/v); Chen et al, 2006] to 38 mM [1.5% (w/v); Stanys et al, 2006]. Actively growing tissues containing a meristem usually yield higher levels of polyploid induction and success has been found using germinating seeds (Pringle and Murray, 1992), ex vitro shoots (Contreras et al, 2007), roots (Kim et al, 2004), embryogenic and non-embryogenic callus (Gao et al, 2002;Suzuki et al, 2005), nodal segments (Chen et al, 2006), cotyledons (Stanys et al, 2006), and hypocotyls (Ascough et al, 2008;De Carvalho et al, 2005).…”
mentioning
confidence: 99%